Analysis of Meaning and Moral Education Values of Al Barzanji's Poetry in The Community Environment Cianjur District - R Tamtam Kamaluddin; Maemunah Sa’diyah; Ibdalsyah; E. Bahruddin (International Journal of Islamic Thought and Humanities, 2024)
The tradition of reading Barzanji's poems in Cianjur District seems to be decreasing and decreasing. The causal factors include 1) the lack of socialization and training from Barzanji speakers towards the younger generation, 2) the lack of interest and attention from the younger generation to learn the recitation of Barzanji's poems, 3) the absence of a specific institution to deepen Islamic cultural art in terms of this is the preservation of the tradition of reading Barzanji's poetry, 4) the rapid flow of infiltration of non-Islamic culture towards the Muslim community so that the Muslim community knows and applies non-Islamic cultures more than the Islamic culture itself. Furthermore, the author conveys that this research will describe the results of data analysis on the meaning and values ​​of Moral Education in the tradition of reading Barzanji's Poems in the community of Cianjur Regency. This method is descriptive. An effort to preserve the Barzanji tradition in the community of Cianjur Regency includes: 1) Improving the learning and training process for the Barzanji Tradition at Majlis Ta'lim and Islamic boarding schools so that the Barzanji tradition can be passed down from generation to generation, 2) Organizing a Barzanji festival periodically with involving religious institutions and schools, especially during religious holidays, 3) making or incorporating Barzanji poetry into teaching materials in Islamic Religious Education or Indonesian language subjects in schools from elementary to tertiary level, 4 ) Carrying out intensive outreach regarding the historicity and meaning of Barzanji's poetry to the wider community both in urban and rural areas.